Christian gacaca and Official gacaca in Post-genocide Rwanda - Denis, Philippe (Journal for the study of religion, 2019)
In October 1998, a think tank of the Rwandan state proposed the establishment of gacaca jurisdictions - popular courts charged with judging the people involved in the genocide against the Tutsi. Lesser known is the Christian gacaca, a conflict resolution mechanism, also inspired by the traditional gacaca, which was established during the same period by the Catholic Church of Rwanda as part of the synodal process leading to the celebration of the 2000 Year Jubilee. This essay describes, on the basis of archival documents and oral testimonies, the genesis of the Christian gacaca and examines how it related to the official gacaca. This pastoral initiative contributed to a relaxation of the tension between church and state that had marked the immediate aftermath of the genocide. The aim of the Christian gacaca was to bring about reconciliation in communities divided by the genocide, by bringing together victims and perpetrators. The task of the official gacaca was to judge and, if the guilt was established, to punish the authors of the genocide crimes. It was also, like in the Christian gacaca, to restore social harmony, but only through a judicial process.